Pelatihan Pemasaran Digital dan Manajemen Usaha untuk Akselerasi Kinerja UKM Pengrajin Bambu di Desa Tirtoadi, Mlati, Sleman - Ratih Kusumawardhani; Ignatius Soni Kurniawan; Nonik Kusuma Ningrum (Jurnal Pengabdian Pada Masyarakat, 2020)
DIGITAL MARKETING TRAINING AND BUSINESS MANAGEMENT FOR THE ACCELERATION OF THE PERFORMANCE OF BAMBOO CRAFTSMEN SMES IN TIRTOADI VILLAGE, MLATI, SLEMAN. This community service program in the forms of training and consulting was carried out for 3 months in Tirtoadi Village, Mlati District, Sleman Regency. Community service participants consisted of bamboo craftsman SMEs and local youth organization (Karang Taruna). Training and counselling material consist of digital marketing, business management, and Intellectual Property Rights (IPR) certification. The training material is in accordance with the problems or constraints experienced by Tirtoadi Village bamboo craftsmen SME. The participants expect that the community service program can be carried out on a regular basis. Several parties involve in the program such as the Tirtoadi Village Government, local youth organization and bamboo craftsmen SME. The training and consulting program contribute to the increase of knowledge related to digital marketing, business management and IPR certification.